Sudden outbreak of metastatic intestinal adenocarcinoma in rainbow trout Oncorhynchus mykiss - Gombač, Mitja; Seničar, Marija; Švara, Tanja; Šturm, Sabina; Dolenšek, Tamara; Tekavec, Kristina; Cerkvenik, Vesna; Schmidt-Posthaus, Heike (Diseases of Aquatic Organisms, 2021)
ABSTRACT: Intestinal adenocarcinomas are uncommon in fishes. To date, they have been reported in zebrafish Danio rerio, blue gularis Fundulopanchax sjostedti, koi carp Cyprinus carpio koi, Atlantic salmon Salmo salar and rainbow trout Oncorhynchus mykiss. Metastases are even rarer and have been observed so far at very low prevalence, only in feed-induced adenocarcinoma in Atlantic salmon and rainbow trout. Intestinal adenocarcinoma with liver and heart metastases and mesenteric invasion was found in approximately 33% of 4 yr old rainbow trout from a Slovene hatchery with 2000 breeding trout. During stripping, lumps in the abdominal cavity were palpated in one-third of the breeding fish some of the fish were anorectic and lethargic, and mortality was slightly increased. Affected trout were euthanized and 4 were submitted for necropsy and histopathology. Necropsy revealed firm, whitish, irregularly lobular masses originating from the intestine. Histologically, the intestinal masses showed a prominent proliferation of tall columnar neoplastic epithelial cells arranged in dense irregular islands or solid areas and papillotubular protuberances. Solid areas of neoplastic cells were also observed in the mesentery of all trout and in the liver of one trout, whereas minute groups of neoplastic cells were seen in the vessels of the intestinal mucosa in all trout and in the myocardium and the liver of one trout. Epithelial origin of neoplastic cells was confirmed by expression of the cytokeratin marker AE1/AE3. The intestinal masses were diagnosed as intestinal adenocarcinoma with mesenteric invasion and metastases to the liver and heart. The cause of intestinal adenocarcinoma was not determined.